Dampak Partisipasi Masyarakat Terhadap Pengelolaan Sampah Di Pantai Pasar Bersehati Kota Manado - Dien, Mirna Sulistianingsih; Rengkung, Leonardus Ricky; Tilaar, Wenny (Sam Ratulangi University, 2023)
The purpose of this research is to analyze the impact of community participation in handling beach cleanliness around Bersehati Market, as well as analyzing the obstacles and challenges of waste management on the beach around Bersehati Market by the relevant government, in this case Calaca Village. The research was conducted from March to April 2022. The research was conducted on the beach of Pasar Bersehati Jl.Nusantara No.17, Calaca, Kec. Wenang, Manado City, North Sulawesi. The data used in this study consisted of primary and secondary data derived from internal government data in this case the Calaca Village Office. Data collection carried out in this research is through literature study and interviews, both of these techniques are carried out in terms of obtaining information relevant to the research. Sampling using nonprobability sampling technique purposive sampling type, namely by selecting sample members who know the problem and agree to provide the information needed, as long as the information can be used as a sample in this study if the respondent is suitable as a data source. Research data analysis is with data reduction activities, data presentation, conclusion drawing. The results showed that community participation in waste management is good enough but cooperation must be further enhanced between the relevant government and the community so that waste management can run optimally, and community participation still needs to be improved.